A CCG expansion in ABCD3 causes oculopharyngodistal myopathy in individuals of European ancestry - Andrea Cortese; Sarah J. Beecroft; Stefano Facchini; Riccardo Curro; Macarena Cabrera-Serrano; Igor Stevanovski; Sanjog R. Chintalaphani; Hasindu Gamaarachchi; Ben Weisburd; Chiara Folland; Gavin Monahan; Carolin K. Scriba; et al. (Nature Communications)
Abstract Oculopharyngodistal myopathy (OPDM) is an inherited myopathy manifesting with ptosis, dysphagia and distal weakness. Pathologically it is characterised by rimmed vacuoles and intranuclear inclusions on muscle biopsy. In recent years CGG • CCG repeat expansion in four different genes were identified in OPDM individuals in Asian populations. None of these have been found in affected individuals of non-Asian ancestry. In this study we describe the identification of CCG expansions in ABCD3, ranging from 118 to 694 repeats, in 35 affected individuals across eight unrelated OPDM families of European ancestry. ABCD3 transcript appears upregulated in fibroblasts and skeletal muscle from OPDM individuals, suggesting a potential role of over-expression of CCG repeat containing ABCD3 transcript in progressive skeletal muscle degeneration. The study provides further evidence of the role of non-coding repeat expansions in unsolved neuromuscular diseases and strengthens the association between the CGG • CCG repeat motif and a specific pattern of muscle weakness.